Epidemiology, clinical characteristics, and risk factors for mortality of early- and late-onset invasive candidiasis in intensive care units in China. Issue 42 (October 2017) - Yang, Yi; Guo, Fengmei; Kang, Yan; Zang, Bin; Cui, Wei; Qin, Bingyu; Qin, Yingzhi; Fang, Qiang; Qin, Tiehe; Jiang, Dongpo; Cai, Bojing; Li, Ruoyu; et al.
Abstract : Abstract: To identify the epidemiology, treatments, outcomes, and risk factors for patients with early- or late-onset invasive candidiasis (EOIC or LOIC) in intensive care units in China. Patients were classified as EOIC (⩽10 days) or LOIC (>10 days) according to the time from hospital admission to IC onset to identify distinct clinical characteristics. There were 105 EOIC cases and 201 LOIC cases in this study. EOIC was related to more severe clinical conditions at ICU admission or prior to IC. Significantly, more cases of Candida parapsilosis infection were found in patients with LOIC than in those with EOIC. The mortality of EOIC was significantly lower than that for LOIC. Sequential Organ Failure Assessment (SOFA) score at ICI diagnosis in the EOIC group and the interval from ICU admission to ICI occurrence in the LOIC group were identified as risk factors for mortality. Susceptibility to the first-line agent was associated with a lower risk of mortality in the LOIC group. The mortality rate was significantly lower in the EOIC group, and there were more cases of non-albicans infection in the LOIC group. Susceptibility to the first-line agent was an important predictor of mortality in the LOIC group. SOFA score at ICI diagnosis in the EOIC group and interval from ICU admission to ICI occurrence in the LOIC group were identified as risk factors for mortality.